HUBUNGAN ANTARA KEMATANGAN BERAGAMA DAN KECERDASAN EMOSIONAL DENGAN DAYA TAHAN TERHADAP STRES - Rahayu, Iin Tri (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2007)
Adolescent age is transition time. There are many changes in the transition time. It is also generating a certain difficult problems. The unready adolescent in response their change in life will make them stress. Therefore, the research aims to know about the relationship between religion maturity and stress resistance, and the relationship between emotional intelligence and stress resistance. Sixty subjects were collected from the psychology department of UIN Malang student. The collecting of data sampling was based on the frame of purposive sampling. The used scale was religion maturity scale, emotional intelligence scale, and stress resistance scale. Data anaysis used in this study was product moment correlation. The result of this study is that there is a positive correlation between religion maturity and stress resistance (p=0.029), and moreover a positive correlation between emotional intelligence and stress resistance can be recovered here (p=0.000).